The Spiderwick: The Seeing Stone - Book 2 - DiTerlizzi, Tony; Black, Holly (New York : Simon and Schuster Books for Young Readers, 2023)
Thanks to the mysterious field guide left behind by their long-lost great-great-uncle Arthur Spiderwick, life for the Grace kids-- Jared, Simon, and Mallory-- is beyond weird. When Simon goes missing, Jared is convinced creatures from the faerie world have something to do with it. Mallory is not convinced. That is, until she and Jared have to contend with a band of menacing, marauding goblins. Simon is clearly in danger, and it's up to Mallory and Jared to save him before it's too late.
Keywords: Goblins -- Juvenile fiction; Danger -- Juvenile fiction; Stepfamilies -- Juvenile fiction; Siblings -- Juvenile fiction; Fairies -- Juvenile fiction; Goblins -- Fiction; Danger -- Fiction; Stepfamilies -- Fiction; Brothers and sisters -- Fiction; Fairies -- Fiction; Fantasy fiction